Salivary glands of Amblyomma cajennense (Acari: Ixodidae): a histological and an ultrastructural overview - Denardi, Sandra Eloisi [UNESP]; Scopinho Furquim, Karim Christina [UNESP]; Bechara, Gervasio Henrique [UNESP]; Camargo-Mathias, Maria Izabel [UNESP] (Springer, 2011)
The present study on the salivary glands of semi-engorged Amblyomma cajennense females has identified the various cell types present in this tissue and allowed its morphohistochemical characterization. Marking techniques were applied to detect polysaccharides (PAS), proteins (bromophenol blue), lipids (Nile blue) and calcium (von Kossa), as well as those of scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The results obtained by TEM showed and confirmed that these individuals' glands are also formed by round acini that are connected to the common excretory duct through acinar and intermediate ducts. Histological data as well as ultrastructural ones showed that the glands are formed by types I, II and III acini. In this study with salivary glands polysaccharides, proteins, lipids and calcium were observed in the cytoplasm and/or cell secretion granules-both free or forming complexes, as the intensity of the marking varied according to the cell as well as the type of acini analyzed, showing the structural and functional complexity of the tick salivary glands, characteristics that give the multifunctional character to this organ.
Keywords: Amblyomma cajennense; Ticks; Salivary gland; Secretory cycle; histochemistry; Ultrastructure